Topoliad of Paolo Rumiz as an inspiration to multi-level learning about Italian culture - Groblińska, Justyna; Kowalik, Katarzyna (Inspiration, 2019)
The article is dedicated to the inspirations coming from literary reportage Leggenda dei monti naviganti by Paolo Rumiz. The Italian writer and journalist describes his journeys across Italian Peninsula through two most important mountain ranges – the Alps and the Apennines. The objective of this expedition was to arrive to places forgotten by tourism and politicians. The conversations with citizens met on the way show the unknown aspects of Italy, different from its common image in culture texts or travel guides. Small mountain villages have to face the demographic and ecological problems. On the other side, they can be proud of particular traditions that should be known and preserved. The journalistic approach of the author is based on experiences of the Polish reportage master – Ryszard Kapuściński. The work presents also numerous analogies with topics of Andrzej Stasiuk’s writing. Paolo Rumiz in his book inspires the readers to look at Italy in unconventional way.